The Variable Association Between Religiosity and Delinquency - Montagnet, Chase (Crime & delinquency, 2023)
Although religion and crime occupies a relatively small space in contemporary criminological research, religious beliefs, and practices are central to classical social theory. This study uses fixed effects models to analyze three waves of panel data from the National Longitudinal Study of Adolescent to Adult Health to examine the relationship between a multidimensional measure of religiosity and several forms of delinquency. The results indicate that the relationship between religiosity and delinquency is offense-specific. While religiosity is inversely related to substance use in the presence of social bonds and predictors of delinquency, its relationship with non-violent delinquency is mixed. Finally, religiosity is not associated with violent offending. The results suggest that renewed interest in religion among criminologists is warranted.